Immigration and the Short- and Long-Term Impact of Improved Prenatal Conditions - Victor Lavy; Analia Schlosser; Adi Shany (Institute of Labor Economics (IZA), 2021)
This paper investigates the effects of immigration from a developing country to a developed country during pregnancy on offspring's outcomes. We focus on intermediate and long-term outcomes, using quasi-experimental variation created by the immigration of Ethiopian Jews to Israel in May 1991. Individuals conceived before immigration experienced dramatic changes in their environmental conditions at different stages of prenatal development depending on their gestational age at migration. We find that females whose mothers immigrated at an earlier gestational age have lower grade repetition and dropout rates in high school. They also show better cognitive performance during primary and middle school and in the high school matriculation study program. As adults, they have higher post-secondary schooling, employment rates, and earnings than those whose mothers migrated at a later stage of pregnancy.
Keywords: I24; I25; I15; J15; 330; prenatal; immigration; human capital